Individuals’ continuance intention of theme park mobile apps - Long, Ting (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2025)
Mobile apps have become a pivotal channel for engaging visitors at leading global attractions, including theme parks, where they significantly enhance visitor satisfaction and generate substantial ancillary revenues. Despite their growing adoption, sustaining users’ continuance intention remains a persistent challenge. While previous studies have extensively examined the factors influencing mobile app continuance intention across various tourism contexts, such as museums and natural landscapes, research on theme park mobile apps (TPMAs) remains limited. In response, this study focuses on investigating the continuance intention of TPMAs through a comprehensive framework, exploring the relationships between user beliefs, user attitudes, and continuance intention. Grounded in well-established theoretical frameworks, including perceived value theory and uses and gratifications theory, the present research categorizes users’ beliefs into five dimensions: aesthetic-related, functional-related, hedonic-related, social-related, and environmental-related beliefs. Additionally, functional-related beliefs are further segmented into five core components: real-time information, map navigation, virtual queues, online ordering, and recommended routes. These beliefs are examined for their influence on user attitudes, specifically satisfaction and delight, as well as their direct impact on continuance intention. Additionally, user characteristics, such as residence type, cultural background, smartphone usage habits, and theme park visit frequency, are explored as moderators shaping these relationships. This study implements a quantitative strategy to identify the key factors which impacts the users’ continuance intention toward TPMAs. Data were collected through three rounds of surveys conducted among individual TPMA users in China and Europe. Two analytical techniques were employed: structural equation modeling (SEM) to test hypothesized relationships, supplemented by fuzzy set qualitative comparative analysis (fsQCA) to identify configurational patterns of antecedents. The main findings of this study reveal that functional beliefs (e.g., perceived usefulness), hedonic beliefs (perceived enjoyment), environmental beliefs (perceived environmental friendliness), and user attitudes (satisfaction and delight) are direct determinants of continuance intention. However, this study did not identify a statistically significant relationship between social beliefs and continuance intention. Besides, satisfaction is influenced by functional and hedonic beliefs, while delight is shaped by functional, hedonic, and aesthetic beliefs. From a configurational perspective, online ordering emerges as a core condition driving continuance intention, while other app functional value, such as real-time information, map navigation, virtual queues, and recommended routes, serve as peripheral conditions. The study makes significant contributions to the field of TPMAs. First, it advances traditional IS research by incorporating environmental beliefs into the analysis of continuance intention. Findings indicate that environmental beliefs significantly impact continuance intention, reflecting users’ growing prioritization of eco-friendly practices. Additionally, beyond satisfaction, this research highlights the critical role of user delight, an often-overlooked attitude in IS studies. Both satisfaction and delight directly influence continuance intention, underscoring the importance of designing user experiences that not only meet functional and hedonic needs but also evoke positive emotions, such as surprise and excitement, to enhance continuance intention of TPMA users. Third, this research contributes to the deeper insight of continued intention outcomes by identifying its positive influence on revisit intention. Finally, user characteristics further enrich prior literature. Residence type and cultural background influence the relationships between beliefs, attitudes, and continuance intention. From a configurational perspective, smartphone usage habits and theme park visit frequency also play critical roles in shaping continuance intention. These insights reveal the critical role of targeted strategies in addressing the heterogeneous needs of distinct user groups. Practically, the results provide actionable insights for theme park operators and app developers aiming to improve user retention via TPMAs.